Implementation of Management Information System At PT. Gojek Indonesia - Rismawati Rismawati; Dewi Urip Wahyuni; Ihsan Zikri Ulfiandi (Journal of Innovative and Creativity, 2025)
The purpose of writing this article is to implement information technology and all community activities in using technology to support operations and management at PT. Gojek Indonesia. Management information systems that are developing at this time provide convenience facilities for technological advances so that they are fast in capturing the information needed for decision making. Information systems in essence existed before the creation of technology that was created at this time, but with a computer-based information system it can provide steps and breakthroughs that are considered fast, precise and also accurate in processing fiber processing data. E-commerce in the current electronic trading system or also called e-commerce or is said to be the distribution, purchase, sale, marketing of goods and services through electronic systems such as the internet such as the internet or television, websites or other computer networks. E-commerce can make things easier by using electronic systems. The application of e-commerce at PT. Gojek Indonesia is well integrated. The results can be seen from the structure of the application offered has provided a conceptual framework form by connecting between processes and also the interface of an e-commerce application, with consumers ordering, the service process until the completion of the services that have been used.